Managing Tensions in Statutory Professional Practice: Living and Working in Rural and Remote Communities - Jervis-Tracey, Paula; Chenoweth, Lesley; McAuliffe, Donna; O'Connor, Barry; Stehlik, Daniela (Australian and International Journal of Rural Education, 2012)
Delivering essential health, education and human services in rural and remote communities remains a critical problem for Australia. When professionals have mandatory responsibilities (e.g. in child protection, law enforcement, education or mental health), tensions can arise between workers and the communities in which they live. This paper reports on part of an Australian Research Council Discovery project which is exploring the management of tensions in work-life balances for professionals in rural and remote communities, as well as investigating the views of community members impacted by the work. In this paper we present findings from the state wide survey of professionals (N ≈ 900) who lived and worked in small communities and who had statutory responsibilities in their role. These data provide valuable insights into practitioners' views about their roles, their preparation for rural practice during education and training, major tensions in juggling allegiance to work and community and the strategies they employ to address these. It is hoped that the study in the long term will offer solutions to the complex medical, legal and social issues that arise for different professional groups in the discharge of their duties. This 3-year project uses both qualitative and quantitative methods to map the terrain of rural and remote statutory work, to explore the nature of the relationships between professionals and communities and examine how professionals manage ethical and allegiance conflicts which arise.